2021
DOI: 10.1038/s41598-021-90740-3
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification of the BASS gene family in four Gossypium species and functional characterization of GhBASSs against salt stress

Abstract: Bile acid sodium symporter (BASS) family proteins encode a class of sodium/solute symporters. Even though the sodium transporting property of BASSs in mammals was well studied, their sodium transportability and functional roles in plant salt tolerance remained largely unknown. Here, BASS family members from 4 cotton species, as well as 30 other species were identified. Then, they were designated as members of BASS1 to BASS5 subfamilies according to their sequence similarity and phylogenetic relationships. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 87 publications
0
5
0
Order By: Relevance
“…The process by which plants maintain normal high K + and low Na + homeostasis under abiotic stress is complex [59]. Based on previous studies, K + / Na + homeostasis is mainly regulated by AKT1, NHX2, SOS1, and HA3 genes [60,61]. We found that 50% HRW treatment significantly up-regulated AKT1 and HA3 genes in lily scales, especially on day 3.…”
Section: Discussionmentioning
confidence: 61%
“…The process by which plants maintain normal high K + and low Na + homeostasis under abiotic stress is complex [59]. Based on previous studies, K + / Na + homeostasis is mainly regulated by AKT1, NHX2, SOS1, and HA3 genes [60,61]. We found that 50% HRW treatment significantly up-regulated AKT1 and HA3 genes in lily scales, especially on day 3.…”
Section: Discussionmentioning
confidence: 61%
“…LOC_Os02g27430 encodes a GRF zinc finger protein family, which generally plays important roles in plant growth and development, as well as abiotic and biotic stress responses [ 39 , 40 , 41 ]. In addition, LOC_Os02g27490 encodes a sodium bile acid symporter family protein, which has been found to be involved in stress resistance [ 42 ]. Thus, these candidate genes are probably related to abiotic and biotic stress resistance and may play a role in resistance to the BPH.…”
Section: Discussionmentioning
confidence: 99%
“…However, BASS proteins are also found in prokaryotes and other eukaryotes, including plants. In plants, there are five BASS subfamilies, BASS1-5 69 .…”
Section: Chloroplastic Pyruvate Transportthe Bass Familymentioning
confidence: 99%